Retrieval of the optical properties of tropospheric aerosols over Athens, Greece combining a 6-wavelength Raman-lidar and the CALIPSO VIS-NIR lidar system: Case-study analysis of a Saharan dust intrusion over the Eastern Mediterranean - Papayannis, Alexandros D.; Chourdakis, Giorgos; Mamouri, Rodanthi-Elisavet (My University, 2007)
The National Technical University of Athens (NTUA) 6-wavelength (355, 387, 407, 532, 607 and 1064 nm) Raman lidar system has been used to derive the aerosol optical properties (e.g. the lidar ratio, the aerosol backscatter and extinction profile) and the water vapour mixing ratios over Athens, Greece during the CALIPSO space lidar overpasses over our area at 355, 532 and 1064 nm. These data have been analyzed for the case of a Saharan dust intrusion over the Eastern Mediterranean, occurred on January 26, 2007, using concurrent aerosol optical depth (AOD) data at 550 nm from the Moderate Resolution Imaging Spectroradiometer (MODIS) and forecasted data from the Dust Regional Atmospheric Modeling (DREAM) model.
Keywords: Aerosols; Optical radar; Backscattering; Dust